1999
DOI: 10.1074/jbc.274.4.2000
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Decreases Na+,K+-ATPase Activity in Pancreatic β-Cells

Abstract: These results demonstrate that glucose inhibits Na ؉ ,K ؉ -ATPase activity in ␤-cells by activating a distinct intracellular signaling network. Inhibition of Na ؉ ,K ؉ -ATPase activity may thus be part of the mechanisms whereby glucose promotes membrane depolarization, an increase in [Ca 2؉ ] i , and thereby insulin secretion in the pancreatic ␤-cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 50 publications
(55 reference statements)
0
21
1
Order By: Relevance
“…Effects of Arachidonic Acid on ␤-Cell Kv2.1 Channel ActivityStimulation of pancreatic islet ␤-cells with glucose induces both the secretion of insulin and hydrolysis of arachidonic acid from membrane phospholipids, and the latter event is thought to facilitate Ca 2ϩ entry and thereby to amplify insulin secretion (7,15,17,18,27,33,36,44). One mechanism whereby arachidonic acid might affect glucose-induced Ca 2ϩ entry into ␤-cells is by modulating activity of delayed rectifier K ϩ channels that limit glucose-induced depolarization of the ␤-cell plasma membrane (2-4, 40 -42, 45-51), and we therefore examined the effects of arachidonic acid on ␤-cell Kv2.1 channel activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of Arachidonic Acid on ␤-Cell Kv2.1 Channel ActivityStimulation of pancreatic islet ␤-cells with glucose induces both the secretion of insulin and hydrolysis of arachidonic acid from membrane phospholipids, and the latter event is thought to facilitate Ca 2ϩ entry and thereby to amplify insulin secretion (7,15,17,18,27,33,36,44). One mechanism whereby arachidonic acid might affect glucose-induced Ca 2ϩ entry into ␤-cells is by modulating activity of delayed rectifier K ϩ channels that limit glucose-induced depolarization of the ␤-cell plasma membrane (2-4, 40 -42, 45-51), and we therefore examined the effects of arachidonic acid on ␤-cell Kv2.1 channel activity.…”
Section: Resultsmentioning
confidence: 99%
“…The phospholipid content of esterified AA is higher in pancreatic islets than in other tissues (23,25,26,29), and arachidonate is hydrolyzed from phospholipids upon stimulation of islets with secretagogues (13,14,27,31,36,44) and accumulates to micromolar concentrations (7,27,28) that are sufficient to modulate delayed rectifier Kv channel FIGURE 5. Effects of the muscarinic agonist carbachol on INS-1 cell-delayed rectifier currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed functions include signaling in secretion (47,48,(52)(53)(54)(55)(56)(57), and BEL attenuates glucose-induced insulin secretion, arachidonate release, and rises in cytosolic [Ca 2ϩ ] in pancreatic islet ␤-cells and insulinoma cells (48,(52)(53)(54)(55)(56)(57).…”
mentioning
confidence: 99%
“…Although it has been shown in studies on tumor ␤-cell lines that a surprisingly small percentage of released radioactivity consists of metabolites (48), a recent study suggested a role for lipooxygenase-12 metabolites in ␤-cell function (57). Further studies need to be conducted to discriminate between AA and its metabolites produced by GIP stimulation of the ␤-cell.…”
Section: ؉mentioning
confidence: 99%